The Effect of using Specialized Exercises to Learning Some Basic Skills of Freestyle Swimming for Ages (9-11) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Specialized exercises are movements or sports exercises that are similar in composition in terms of the composition of the motor performance of strength, speed, and movement path. They consist of movements that are similar in their paths to competition movements, so that their type matches the characteristics and ability of the player and depends on certain parts of the body’s muscles that are specific to the activity or sport. Specific movements that include movements similar to those of an event or sport, the importance of the study lies in the use of specialized exercises in learning some basic skills in freestyle swimming for ages (9-11), since the researcher saw that players of all ages (9–11) did not utilize the specific exercises in the game that required these abilities, and that other teaching approaches should be used. The researcher made the decision to conduct an experiment to add contemporary workouts in order to get the greatest outcomes, including specialized exercises, effectively to know the extent of its impact on the knowledge of some basic skills in freestyle swimming. “The researcher used the experimental approach with two groups, the control and experimental groups, with pre- and post-tests.” The researcher identified his research population in an intentional way as the players of the Waves Academy for teaching and training swimming in Babil Governorate, who number (24). A budding swimmer, the research sample was chosen randomly, distributed equally into two groups: the group the control group (8) swimmers and the experimental group (8) swimmers. An exploratory experiment was conducted on a sample of (4) junior swimmers, after which educational units were designed using specialized exercises. The study was conducted over a period of eight weeks, with two 45-minute instructional units each week. Subsequently, the post-test was administered, the experiment was run for a month, and the researcher utilized the bag. Using statistics to get outcomes.